Low Molecular Weight Heparin Therapy: Is Monitoring Needed? - Boneu, B (Thrombosis and Haemostasis, 1994)
Recent meta-analyses indicate that low molecular weight heparins (LMWH) are more effective than unfractionated heparin (UH) in preventing and treating deep vein thrombosis. This article presents the arguments for and against the need for laboratory monitoring. At the present time, the only tests currently available for monitoring LMWH therapy are those which measure the anti Xa activity in the plasma. Due to lower binding to plasma proteins and to cell surfaces,the plasma anti Xa activity generated by a given dose of LMWH is more predictable than for UH.Some clinical trials suggest that LMWH delivered at the recommended dose expose the patient to less bleeding risk than UH. Several . meta-analyses indicate comparable risk while any overdose unaccept-ably increases the haemorrhagic risk. The lowest dose of LMWH still effective in treating established DVT is presently unknown; some reports indicate that inadequate doses of LMWH are associated with a lack of efficacy for prevention. An overview of the published clinical trials indicates that the LMWH dose has never been monitored for prevention of DVT. In the treatment of established DVT, several trials have been performed without any monitoring, while in others the dose was adapted to target a given anti Xa activity. These considerations suggest that in prevention of DVT, monitoring the dose is not required. In the treatment of established DVT, considering the haemorrhagic risk of LMWH, the risk of undertreating the patient and the absence of large clinical trials comparing the advantages of monitoring the dose or not, it might be useful to check anti Xa activity at least once at the beginning of the treatment but the need for this initial check remains to be established. Because a large proportion of patients will be in the desired range, dose adjustments will be far less frequent than for UH.